Subwavelength wave manipulation in a thin surface-wave bandgap crystal - Gao, Zhen (2019)
It has been recently reported that the unit cell of wire media metamaterials can be tailored locally to shape the flow of electromagnetic waves at subwavelength scales [Lemoult et al., Nature Physics 9, 55-60 (2013)]. However, such bulk structures have a thickness of at least the order of wavelength, thus hindering their applications in the on-chip compact plasmonic integrated circuits. Here, based upon a Sievenpiper “mushroom” array [Sievenpiper et al., IEEE Trans. Microwave Theory Tech. 47, 2059 (1999)] which is compatible with the standard printed circuit board technology, we propose and experimentally demonstrate the subwavelength manipulation of surface waves on a thin surface-wave band-gap crystal with a thickness much smaller than the wavelength (1/30th of the operating wavelength). Functional devices including T-shaped splitter and sharp bend are constructed with good performance.